The Effect Plant Media Composition on the Growth and Production Some Varieties Strawberry - Sitorus, Efbertias; Sihombing, Parsaoran; Panataria, Lince Romauli; Saragih, Meylin Kristina; Manurung, Agnes Imelda (ITScience (Information Technology and Science), 2024)
This research was conducted in Barus Jahe Village, Barus Jahe District, Karo Regency, North Sumatra, with an altitude of 1,367 meters above sea level. This study aims to determine the effect of the composition of the planting medium and several varieties on the production and growth of strawberry plants. The design used in this research is a Factorial Split Plot Design (RPT), which consists of two factors. The first factor is the main plot, Variety (V), with 3 levels: V1 = California, V2 = Local Bandung, and V3 = Local Brastagi. The second factor is the subplot, namely Planting Media Composition (M), which consists of Soil: Charcoal Husk: Chicken Manure, namely: M1= 1:1:1, M2= 2:1:1, M3= 1:2:1, and M4= 2:1:2.The variables observed were plant height, plant wet weight and plant dry weight, fruit weight and sugar content (Brix). Analysis of variance was used to test the effect of treatment and mean differences between treatments; honest significant difference tests, regression, and correlation were carried out at a test level of 5%. The research results showed that the composition of the planting media had no significant effect on the observed parameters. However, in some varieties, V1 (California) has a substantial impact on fruit weight and sugar content (Brix), and V2 (Local Bandung) has a significant effect on plant height, wet weight, and dry weight.